2019
DOI: 10.25165/j.ijabe.20191204.4608
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subsoiling on working quality and total power consumption of high stubble straw returning machine

Abstract: Straw returning into field is a direct and effective measure to reduce the straw burning and improve the soil organic matter content. Straw returning directly to field needs higher performance machines, especially under the condition of large amount of straw in the field is more difficult. Therefore, the model of conservation tillage by combination of subsoiling and straw returning was studied. Experiments on combined tillage machine for effect of subsoiling on working quality and total power consumption for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…According to the article's method [18], soil moisture was measured in the 0-1030 cm layer. The stubble sunflower height was measured diagonally along the field using a ruler.…”
Section: Main Mode Operation Of the Plow-chopping Unitmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the article's method [18], soil moisture was measured in the 0-1030 cm layer. The stubble sunflower height was measured diagonally along the field using a ruler.…”
Section: Main Mode Operation Of the Plow-chopping Unitmentioning
confidence: 99%
“…Sometimes, machines with active working devices in the form of cutters are used [18]. Moreover, they are even used in the controlled traffic farming system [19].…”
Section: Introductionmentioning
confidence: 99%
“…A study reported 575 million liters of annual fuel loss in the USA due to the mismanagement of off-road vehicles at the soil-wheel interfaces in agricultural applications alone [3]. The energy lost in wheel soil interaction and the driving process is used to wear the tires and to compact the soil that causes detrimental effects on crop production [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The traditional crawler of combine harvester was unilateral brake and unilateral steering. This steering method could result in field soil damage with crawling sinking into soft soil [8,9] . The status quo of traditional crawler steering is shown in Figure 1.…”
Section: Introduction mentioning
confidence: 99%